Profiling the dynamics of trust & distrust in social media: A survey study - Zhang, Yixuan; Wang, Yimeng; Yongsatianchot, Nutchanon; Gaggiano, Joseph D.; Nurul Mubinah, Suhaimi; Okrah, Anne; Kim, Miso; Griffin, Jacqueline A.; Parker, Andrea Grimes (Association for Computing Machinery, 2024)
In the era of digital communication, misinformation on social media threatens the foundational trust in these platforms. While myriad measures have been implemented to counteract misinformation, the complex relationship between these interventions and the multifaceted dynamics of trust and distrust on social media remains underexplored. To bridge this gap, we surveyed 1,769 participants in the U.S. to gauge their trust and distrust in social media and examine their experiences with anti-misinformation features. Our research demonstrates how trust and distrust in social media are not simply two ends of a spectrum; but can also co-exist, enriching the theoretical understanding of these constructs. Furthermore, participants exhibited varying patterns of trust and distrust across demographic characteristics and platforms. Our results also show that current misinformation interventions helped heighten awareness of misinformation and bolstered trust in social media, but did not alleviate underlying distrust. We discuss theoretical and practical implications for future research.